Endophthalmitis in an Immunocompromised Patient - Katarina Janicijevic, Dejan Vulovic, Mirjana A. Janicijevic Petrovic, Tatjana Sarenac Vulovic; Predrag Jovanovic, Dragan Vujic (Pakistan Journal of Ophthalmology, 2018)
Purpose: The goal of manuscript was to report a case of mixed infection eye in an immunocompromised patient. Case report: A case of bilateral Cytomegalovirus (CMV) retinitis with endogenous endophthalmitis in the left eye in an immunocompromised drug user is reported. Fundus examination showed retinitis of the right eye. Slit lamp examinations revealed endogenous endophthalmitis of left eye. Authors applied disposable therapeutic modules. Conclusion: Cytomegalovirus retinitis is an infection of the retina in an immunocompromised patients localised to the back of eye. Untreated endogenous endophthalmitis leads to progressive destruction of almost all eye structures and poor visual outcome. The prognosis is dependent on adequate antiviral therapy and immune competence of the patient. Ganciclovir treatment was effective in our case.